N-UPTAKE AND SPINACH INITIAL GROWTH UNDER PLASTIC-TUNNEL AND APPLICATION OF ORGANIC FERTILIZERS - Sri Endah Prasetyowati; Yacobus Sunaryo; Zamroni Zamroni (Agros Journal of Agriculture Science, 2013)
Research conducted in experimental field of Agricultural Faculty of Sarjanawiyata Tamansiswa University from October until November, 2010. Experiment used factorial 2x4 arranged in Split-Plot Design. Main-plot was environmental planting condition: open field and plastic tunnel. Sub-plot was fertilizer: urea, NPK, chicken manure, Bokashi. Treatments replicated in three replications. Observations: fresh weight, dry weight, N total, and Cation Exchange Capacity (CEC). Result: no interactions between environmental planting conditions and fertilizer various on fresh weight, dry weight, and CEC. There was interaction between environmental planting conditions and fertilizer various on N total content. Plastic tunnel resulted higher both on fresh weight and dry weight than that of open field. Compare to open field, there was no significantly different effect of plastic tunnel on CEC. Application of Bokashi could produce fresh weight as well as dry weight higher than that of application of chicken manure, NPK as well as urea. Under open field condition, there were no significantly different on N total content of the plants treated by urea, NPK, chicken manure as well as bokashi. Whereas under plastic tunnel condition, both application of bokashi and NPK resulted in higher N total content than application of chicken manure as well as urea. Key-words: spinach; plastic; fertilizer1 Author’s address for correspondence: Sri Endah Prasetyowati, Agriculture Faculty of Sarjanawiyata Tamansiswa University Yogyakarta, Indonesia. E-mail: info@fp_ustjogja.ac.id